Large Impacts, Past and Future, of Ozone‐Depleting Substances on Brewer‐Dobson Circulation Trends: A Multimodel Assessment. Issue 13 (2nd July 2019) - Polvani, L. M.; Wang, L.; Abalos, M.; Butchart, N.; Chipperfield, M. P.; Dameris, M.; Deushi, M.; Dhomse, S. S.; Jöckel, P.; Kinnison, D.; Michou, M.; Morgenstern, O.; et al.
Abstract: Substantial increases in the atmospheric concentration of well‐mixed greenhouse gases (notably CO2 ), such as those projected to occur by the end of the 21st century under large radiative forcing scenarios, have long been known to cause an acceleration of the Brewer‐Dobson circulation (BDC) in climate models. More recently, however, several single‐model studies have proposed that ozone‐depleting substances might also be important drivers of BDC trends. As these studies were conducted with different forcings over different periods, it is difficult to combine them to obtain a robust quantitative picture of the relative importance of ozone‐depleting substances as drivers of BDC trends. To this end, we here analyze—over identical past and future periods—the output from 20 similarly forced models, gathered from two recent chemistry‐climate modeling intercomparison projects. Our multimodel analysis reveals that ozone‐depleting substances are responsible for more than half of the modeled BDC trends in the two decades 1980–2000. We also find that, as a consequence of the Montreal Protocol, decreasing concentrations of ozone‐depleting substances in coming decades will strongly decelerate the BDC until the year 2080, reducing the age‐of‐air trends by more than half, and will thus substantially mitigate the impact of increasing CO2 . As ozone‐depleting substances impact BDC trends, primarily, via the depletion/recovery of stratospheric ozone over the South Pole, they impart seasonal and hemispheric asymmetries to the trends which may offer opportunities for detection in coming decades. Key Points: Impacts of ozone‐depleting substances (ODS) on Brewer‐Dobson circulation trends are analyzed in 20 chemistry‐climate models For the period 1980–2000 ODS have contributed more than half (roughly 60%) of the stratospheric age‐of‐air trends For the period 2000–2080 models show that decreasing ODS levels will substantially decelerate the BDC